2016
DOI: 10.1371/journal.ppat.1005886
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal 18 Amino Acid Region of Dengue Virus NS5 Regulates its Subcellular Localization and Contains a Conserved Arginine Residue Essential for Infectious Virus Production

Abstract: Dengue virus NS5 is the most highly conserved amongst the viral non-structural proteins and is responsible for capping, methylation and replication of the flavivirus RNA genome. Interactions of NS5 with host proteins also modulate host immune responses. Although replication occurs in the cytoplasm, an unusual characteristic of DENV2 NS5 is that it localizes to the nucleus during infection with no clear role in replication or pathogenesis. We examined NS5 of DENV1 and 2, which exhibit the most prominent differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
139
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 74 publications
(161 citation statements)
references
References 66 publications
12
139
1
2
Order By: Relevance
“…A), suggesting that the R681 mutations disrupting the dimer–dimer interface do not affect NS5 protein stability in cells. ZIKV NS5 WT has been demonstrated to localize into distinct spherical bodies within the nucleus , while DENV‐2 NS5 exhibited more diffused‐nuclear localization . Interrogation of the ZIKV NS5 mutants’ subcellular localization by CLSM revealed that the R681A mutant exhibited a mix phenotype of diffused‐nuclear localization similar to DENV‐2 NS5, and distinct nuclear body formation in the transfected cells (Fig.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…A), suggesting that the R681 mutations disrupting the dimer–dimer interface do not affect NS5 protein stability in cells. ZIKV NS5 WT has been demonstrated to localize into distinct spherical bodies within the nucleus , while DENV‐2 NS5 exhibited more diffused‐nuclear localization . Interrogation of the ZIKV NS5 mutants’ subcellular localization by CLSM revealed that the R681A mutant exhibited a mix phenotype of diffused‐nuclear localization similar to DENV‐2 NS5, and distinct nuclear body formation in the transfected cells (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Differential subcellular localization of NS5 has been reported for DENV [4,6] where it is predominantly nuclear for DENV-2, -3, and -4, and mostly cytoplasmic for DENV-1 [6]. More recently, it was demonstrated that the closely related flavivirus, ZIKV NS5 formed supramolecular nuclear bodies that were distinct from DENV-2 NS5 despite being nuclear localized [8,9,56].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Such mechanism of oligomer variations is common e.g. for the family of peroxiredoxins, which alter between catalytically active dimers and decamers or even dodecamers depending on redox regulation , the Dengue nonstructural protein NS5 proposed to switch from a monomer to dimer during the process of the replication complex , or the mycobacterial aspartate decarboxylase PanD, required for pantothenate and CoenzymeA (CoA) biosynthesis, described to occur in a tetrameric and octameric state . Furthermore, NADPH induces tetramer formation with inactivation of the human dihydrolipoamide dehydrogenase or causing an increase in activity of the related glutathione reductase of Cyanobacterium and Spirulina maxima have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…312 Elegant structural and reverse genetic studies indicate the possibility of NS5 dimerization 313 and position the C-terminal 18 residues close to the thumb subdomain, which could be important for initiation of RNA synthesis. 314 …”
Section: Biochemistry and Molecular Biology Of Flavivirusesmentioning
confidence: 99%